Salicylic acid regulates adventitious root formation via competitive inhibition of the auxin conjugation enzyme CsGH3.5 in cucumber hypocotyls - Dong, Chun-Juan; Liu, Xin-Yan; Xie, Lu-Lu; Wang, Ling-Ling; Shang, Qing-Mao (Planta, 2020)
Main conclusion Exogenous SA treatment at appropriate concentrations promotes adventitious root formation in cucumber hypocotyls, via competitive inhibiting the IAA-Asp synthetase activity of CsGH3.5, and increasing the local free IAA level. Adventitious root formation is critical for the cutting propagation of horticultural plants. Indole-3-acetic acid (IAA) has been shown to play a central role in regulating this process, while for salicylic acid (SA), its exact effects and regulatory mechanism have not been elucidated. In this study, we showed that exogenous SA treatment at the concentrations of both 50 and 100 µM promoted adventitious root formation at the base of the hypocotyl of cucumber seedlings. At these concentrations, SA could induce the expression of CYCLIN and Cyclin-dependent Kinase ( CDK ) genes during adventitious rooting. IAA was shown to be involved in SA-induced adventitious root formation in cucumber hypocotyls. Exposure to exogenous SA led to a slight increase in the free IAA content, and pre-treatment with the auxin transport inhibitor 1-naphthylphthalamic acid (NPA) almost completely abolished the inducible effects of SA on adventitious root number. SA-induced IAA accumulation was also associated with the enhanced expression of Gretchen Hagen3.5 ( CsGH3.5 ). The in vitro enzymatic assay indicated that CsGH3.5 has both IAA- and SA-amido synthetase activity and prefers aspartate (Asp) as the amino acid conjugate. The Asp concentration dictated the functional activity of CsGH3.5 on IAA. Both affinity and catalytic efficiency ( K cat / K m ) increased when the Asp concentration increased from 0.3 to 1 mM. In contrast, CsGH3.5 showed equal catalytic efficiency for SA at low and high Asp concentrations. Furthermore, SA functioned as a competitive inhibitor of the IAA-Asp synthetase activity of CsGH3.5. During adventitious formation, SA application indeed repressed the IAA-Asp levels in the rooting zone. These data show that SA plays an inducible role in adventitious root formation in cucumber through competitive inhibition of the auxin conjugation enzyme CsGH3.5. SA reduces the IAA conjugate levels, thereby increasing the local free IAA level and ultimately enhancing adventitious root formation.